2007
DOI: 10.1021/jf071724y
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Approach to Biodiesel Production

Abstract: The need for alternative energy sources that combine environmental friendliness with biodegradability, low toxicity, renewability, and less dependence on petroleum products has never been greater. One such energy source is referred to as biodiesel. This can be produced from vegetable oils, animal fats, microalgal oils, waste products of vegetable oil refinery or animal rendering, and used frying oils. Chemically, they are known as monoalkyl esters of fatty acids. The conventional method for producing biodiesel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
209
0
15

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(238 citation statements)
references
References 83 publications
(128 reference statements)
4
209
0
15
Order By: Relevance
“…Despite these disadvantages, enzyme catalysed process used for biodiesel production is nowadays considered as an environmentally-friendly alternative having good opportunity to be highly commercialized when new, less expensive and more efficient, biocatalysts will be available (7,42), especially with implementation of recombinant DNA technology (43).…”
Section: Enzymatic Catalytic Transesterificationmentioning
confidence: 99%
“…Despite these disadvantages, enzyme catalysed process used for biodiesel production is nowadays considered as an environmentally-friendly alternative having good opportunity to be highly commercialized when new, less expensive and more efficient, biocatalysts will be available (7,42), especially with implementation of recombinant DNA technology (43).…”
Section: Enzymatic Catalytic Transesterificationmentioning
confidence: 99%
“…27 Regeneration of the activity of deactivated immobilized C. antarctica lipase has been demonstrated. 2 The production and stability of immobilized C. antarctica lipase for routine cost-effective application in an industrial biorefinery are under investigation in our laboratory.…”
Section: Specific Activity and Ethyl Ester Production Frommentioning
confidence: 99%
“…2,20e22 Differences have been observed in the catalytic activity of a lipase enzyme immobilized on different supports having different functional groups on their surface, allowing either physical or chemical adsorption. 2,19,23 Surface structure of the support can affect enzyme activity through direct effects (type, strength, and orientation of enzyme-support interactions) or indirect effects (substrate-product interaction with the support affecting substrate-product partitioning between medium and binding site). In one study, the lowest loading of enzyme on a support showed the highest catalytic efficiency (activity of loaded protein).…”
Section: Introductionmentioning
confidence: 99%
“…14,165,166,170 Porém, isso deve ser melhor avaliado, uma vez que mesmo se o rendimento da transformação fosse 100%, fato incomum na catálise enzimática até o presente, após a separação da glicerina, a fase que contém os ésteres deverá ser submetida à evaporação para a completa remoção do álcool que foi usado em excesso. No caso de ter sido usado um cossolvente como, por exemplo, hexano 171,172 este também deverá ser removido. os ésteres resultantes ainda poderão conter glicerina residual dissolvida, a qual deverá ser removida em uma etapa de purificação obrigatória para enquadrar o produto nas especificações de qualidade EN 14214, 6 ASTm 6751 D 4 ou ANP 07/2008.…”
Section: Catálise Heterogênea áCida E Alcalinaunclassified